PENGARUH CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA, JAKARTA - Mulia Saputra (Journal of Indonesian Applied Economics, 2010)
Researches on the influence of corporate governance on firm value have been widelyconducted, however results inconsistency occurred. Corporate governance , whichin this case is ownership structure assessed by present of  ownership structure. Thisresearch uses 150 manufacturing firms listed on the Jakarta Stock Exchange during2002 - 2005 as samples with 600 observation Hypothesis is tested using regressionanalysis  The  firm  value measured  using  Tobin’s Q.  Results  indicate  that  familyownership,  institution ownership and  foreign ownership was not significant effecton firm value. but managerial ownership, have a significant and positive effect onfirm value.Keywords: Family Ownership, Institution ownership, managerial ownership, foreignownership and firm value